2021
DOI: 10.1038/s41598-021-97804-4
|View full text |Cite
|
Sign up to set email alerts
|

Model-based analysis of multi-UAV path planning for surveying postdisaster building damage

Abstract: Emergency responders require accurate and comprehensive data to make informed decisions. Moreover, the data should be acquired and analyzed swiftly to ensure an efficient response. One of the tasks at hand post-disaster is damage assessment within the impacted areas. In particular, building damage should be assessed to account for possible casualties, and displaced populations, to estimate long-term shelter capacities, and to assess the damage to services that depend on essential infrastructure (e.g. hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…In addition, comparing the accuracy with that achieved in the previous study demonstrated significant improvement over the results of using accurate Japanese real estate images with built-year and building-structure classifications of 0.367 and 0.786, respectively [17]. A previous study using SVI data achieved an accuracy of 0.869-0.871 in material classification in Chile [25] and an accuracy of 0.614 and 0.81 in built age classification in Austria and in Amsterdam, respectively [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30].…”
Section: B Classification Of the Built Year And Structure Of Individu...mentioning
confidence: 77%
See 1 more Smart Citation
“…In addition, comparing the accuracy with that achieved in the previous study demonstrated significant improvement over the results of using accurate Japanese real estate images with built-year and building-structure classifications of 0.367 and 0.786, respectively [17]. A previous study using SVI data achieved an accuracy of 0.869-0.871 in material classification in Chile [25] and an accuracy of 0.614 and 0.81 in built age classification in Austria and in Amsterdam, respectively [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30].…”
Section: B Classification Of the Built Year And Structure Of Individu...mentioning
confidence: 77%
“…Although few studies have focused on classifying the built year, several methods have been proposed to classify the number of floors and structures based on field surveys [13], [14], aerial photographs [15], [16], real estate images [17], [18], [19], and methods that use attributes (number of floors and area) of statistical data and GIS building data [20], [21], [22], [23]. However, real estate images bias data collection by essentially covering only trading estate buildings and fewer old buildings.…”
mentioning
confidence: 99%
“…Nagasawa et al [38] proposed a multi-UAV trajectory planning method in the case of three-dimensional building damage investigation or disaster, which combined the fuzzy c-means method of assigning positioning points to UAVs and the A* algorithm to calculate the access sequence of each UAV camera positioning point so as to obtain the feasible trajectory of multiple UAVs, which solves the problem of multi-UAV coverage trajectory planning for the 3D reconstruction of damaged buildings after disasters.…”
Section: A* Algorithmmentioning
confidence: 99%
“…There are algorithms based on multiagent reinforcement learning [6], on Multi-Agent Path Planning (MAPF) [11], with evolutionary algorithms [9], graph [4] and grid-based [7] solutions, combinations of algorithms for solving partial problems [12]. Multi-objective and multi-UAV path planning [13] are also available as well as UAV path planning to ensure the least time within the effective detection range of radar [14]. Some solutions have collision avoidance capabilitiese.g.…”
Section: State Of the Artmentioning
confidence: 99%